The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1966
DOI: 10.1111/j.1365-2494.1966.tb00473.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF CUTTING COCKSFOOT (DACTYLIS GLOMERATA L.) GROWN FOR PRODUCTION OF SEED

Abstract: An experiment is described in which cocksfoot, grown for production of seed, was cut annually for 3 years in either autumn, winter or spring. No significant increases in yield of seed/ac were obtained from any treatment compared with an uncut control, and a cut in late April in one year seriously reduced the yield of seed. Additional N applied after a defoliation in October did not increase the yield of seed compared with that from plots which were cut at the same time but not fertilized. The production of til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1966
1966
1996
1996

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It was found that often only a small proportion of the tillers became reproductive, and the percentage of tillers that produced inflorescences fell each year as the plants aged and the number of tillers per plant increased. Applied N-even applications up to 6 times as large as conventional applications of 100 to 200 kg N/ha-had little effect on the proportion of tillers that produced inflorescences, although the number of tillers, and therefore of infiorescences, per plant was increased by N. When the penetration of light into the plants was increased by defoliating at a height of 6-5 cm above ground, the percentage of tillers which produced inflorescences in the first year was also increased, but the effect diminished in subsequent years when the number of tillers per plant was greater (8).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It was found that often only a small proportion of the tillers became reproductive, and the percentage of tillers that produced inflorescences fell each year as the plants aged and the number of tillers per plant increased. Applied N-even applications up to 6 times as large as conventional applications of 100 to 200 kg N/ha-had little effect on the proportion of tillers that produced inflorescences, although the number of tillers, and therefore of infiorescences, per plant was increased by N. When the penetration of light into the plants was increased by defoliating at a height of 6-5 cm above ground, the percentage of tillers which produced inflorescences in the first year was also increased, but the effect diminished in subsequent years when the number of tillers per plant was greater (8).…”
Section: Introductionmentioning
confidence: 91%
“…It was assumed, therefore, that competition between plants was more important than competition within plants in determining the proportion of tillers that produced inflorescences. In the defoliation experiment (8), both penetration of light and the rate of application of N were varied, but there was no indication that N became limiting when the penetration of light was increased. However, in that experiment the amount of light reaching the smaller tillers was increased but the total interception of light by the whole plant was reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lambert (5) reporting on defoliation effects on cocksfoot, also found reduced yield potential after cutting and associated this result with a shortage of metabolites, which brought about a restriction in fioral parts or influenced the filling of the seed.…”
Section: Discussionmentioning
confidence: 99%
“…and thereby extend knowledge of the capacity of tillers arising on different dates to produce inflorescences from an annual basis (2,5,6,7,13) to the complete life-span of more persistent tillers. Evidence demonstrating which tillers in the plants produced inflorescences, and the dates of origin of such tillers, is presented in this communication.…”
Section: Introductionmentioning
confidence: 99%